The origin of high δ18O zircons: marbles, megacrysts, and metamorphism - Cavosie, Aaron; Valley, J.; Kita, N.; Spicuzza, M.; Ushikubo, T.; Wilde, Simon (Springer, 2011)
The oxygen isotope ratios (δ18O) of most igneous zircons range from 5 to 8‰, with 99% of published values from 1345 rocks below 10‰. Metamorphic zircons from quartzite, metapelite, metabasite, and eclogite record δ18O values from 5 to 17‰, with 99% below 15‰. However, zircons with anomalously high δ18O, up to 23‰, have been reported in detrital suites; source rocks for these unusual zircons have not been identified. We report data for zircons from Sri Lanka and Myanmar that constrain a metamorphic petrogenesis for anomalously high δ18O in zircon. A suite of 28 large detrital zircon megacrysts from Mogok (Myanmar) analyzed by laser fluorination yields δ18O from 9.4 to 25.5‰. The U–Pb standard, CZ3, a large detrital zircon megacryst from Sri Lanka, yields δ18O = 15.4 ± 0.1‰ (2 SE) by ion microprobe. A euhedral unzoned zircon in a thin section of Sri Lanka granulite facies calcite marble yields δ18O = 19.4‰ by ion microprobe and confirms a metamorphic petrogenesis of zircon in marble. Small oxygen isotope fractionations between zircon and most minerals require a high δ18O source for the high δ18O zircons. Predicted equilibrium values of Δ18O(calcite-zircon) = 2–3‰ from 800 to 600°C show that metamorphic zircon crystallizing in a high δ18O marble will have high δ18O. The high δ18O zircons (>15‰) from both Sri Lanka and Mogok overlap the values of primary marine carbonates, and marbles are known detrital gemstone sources in both localities.The high δ18O zircons are thus metamorphic; the 15–25‰ zircon values are consistent with a marble origin in a rock-dominated system (i.e., low fluid(external)/rock); the lower δ18O zircon values (9–15‰) are consistent with an origin in an external fluid-dominated system, such as skarn derived from marble, although many non-metasomatized marbles also fall in this range of δ18O. High δ18O (>15‰) and the absence of zoning can thus be used as a tracer to identify a marble source for high δ18O detrital zircons; this recognition can aid provenance studies in complex metamorphic terranes where age determinations alone may not allow discrimination of coeval source rocks. Metamorphic zircon megacrysts have not been reported previously and appear to be associated with high-grade marble. Identification of high δ18O zircons can also aid geochronology studies that seek to date high-grade metamorphic events due to the ability to distinguish metamorphic from detrital zircons in marble.